Kinetic and kinematic aspects of the vertical jump related to overreaching: A systematic review - Ross, J. A.; Jelmini, J. D.; Leary, B. K.; Hoch, M. C.; Heebner, N. R. (Strength and Conditioning Journal, 2024)
Extended overreaching without recovery carries risks of nonfunctional overreaching and overtraining. Coaches mitigate these risks by screening for overreaching, often using jump testing; however, many are uncertain about which jump variables to measure. A systematic review was conducted to identify jumping kinetic and kinematic variables associated with heightened training stress. Manuscripts were included if they monitored overreaching in healthy, adult athletes at National Level or above using an unloaded vertical jump test; and excluded if they did not report measured kinetic/kinematic variables, did not include sufficient data to calculate effect sizes (ES) and confidence intervals (95% CI) or were not available in English. Fourteen manuscripts met inclusion/exclusion criteria. Most studies had a low (71.4%) or moderate (21.4%) risk of bias. Twenty-nine unique outcome measures were reported with 11 reported in multiple studies. The most reported measures were the ratio of flight time to contraction time (15 ES reported), jump height (JH, 12 ES), mean power (7 ES), peak power (PP, 7 ES), mean velocity (5 ES), and peak force (PF, 5 ES). PP, PF, and JH demonstrated the most consistent negative alterations. Coaches should consider metrics that include changes in jump strategy alongside JH in jump screening.